2016
DOI: 10.1002/pa.1620
|View full text |Cite
|
Sign up to set email alerts
|

E‐government and public service quality in Ghana

Abstract: This article contributes to the growing discourse on the potential of e‐government to transform the operations of public sector institutions, thereby improving public services. It does so by conceptualizing public service quality into efficiency, economy (cost reduction), customer satisfaction, and service accessibility and draws on qualitative data from the Ghanaian narrative for illustration. As previous studies have demonstrated, this study also affirms the potential of e‐government in improving public serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 44 publications
0
32
0
Order By: Relevance
“…The study found some limitations to the full deployment of e‐government in the study organizations that were mainly issues of the capacity of target users, low resident awareness of e‐government tools at the MMDAs, financial inefficiencies, and the related infrastructural deficits. These limitations had also been identified by other studies (Addo, ; Alemna & Sam, ; Osei‐Kojo, ). This finding is in sync with the 2016 E‐Government Survey, which suggests that a major setback with Ghana's e‐government development is the lack of supporting infrastructure (United Nations, ).…”
Section: Discussion Of Findingsmentioning
confidence: 66%
See 2 more Smart Citations
“…The study found some limitations to the full deployment of e‐government in the study organizations that were mainly issues of the capacity of target users, low resident awareness of e‐government tools at the MMDAs, financial inefficiencies, and the related infrastructural deficits. These limitations had also been identified by other studies (Addo, ; Alemna & Sam, ; Osei‐Kojo, ). This finding is in sync with the 2016 E‐Government Survey, which suggests that a major setback with Ghana's e‐government development is the lack of supporting infrastructure (United Nations, ).…”
Section: Discussion Of Findingsmentioning
confidence: 66%
“…It is argued that ICT advancements have significantly affected all aspects of social life, as the proper implementation of e‐government strategy could enhance the effectiveness of local government functions in Ghana (Misuraca, ). Apparently, the opportunities provided by governments as a result of introducing ICT could lead to increased operational efficiency and better quality of services provided by government agencies (Osei‐Kojo, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was important to evaluate user satisfaction for quality due to its significant influence in adopting and spreading technology in a community [13]. Therefore, the measurement of the user satisfaction level proposed in this model also paid attention to aspects of the public value of net benefits and the use of technology due to the potential of community satisfaction to improve public services through the utilization of electronic facilities [15].…”
Section: Information Qualitymentioning
confidence: 99%
“…Nonetheless, there is a limited body of literature that evaluates the role of ICT and e‐government in revenue mobilization at the national and local levels. Also, some of the studies that have focused on the use of ICTs in public institutions have neglected local authorities like MMDAs (Ohemeng & Ofosu‐Darkwah, ; Osei‐Kojo, ), in spite of the inclusion of Accra Metropolitan Assembly (AMA) in the most recent World Bank‐funded e‐Ghana Project in 2008. There is the need for researchers to fill this void, by undertaking studies, which seek to evaluate the implementation of e‐government strategies by local institutions in Ghana.…”
Section: Introductionmentioning
confidence: 99%